2015
DOI: 10.1021/acs.nanolett.5b03057
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Anisotropic Growth and Atomic-Scale Structure of Shape-Controlled Octahedral Pt–Ni–Co Alloy Nanocatalysts

Abstract: Multimetallic shape-controlled nanoparticles offer great opportunities to tune the activity, selectivity and stability of electrocatalytic surface reactions. However, in many cases, our synthetic control over particle size, composition and shape is limited requiring trial and error.Deeper atomic-scale insight in the particle formation process would enable more rational syntheses. Here we exemplify this using a family of trimetallic PtNiCo nanooctahedra obtained via a low-temperature, surfactant-free solvotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 47 publications
6
114
1
2
Order By: Relevance
“…The ability of nickel and cobalt to alloy with each other and with platinum in various ratios enables their potential use in ternary Pt‐Ni‐Co catalysts . The ORR activity of cubo‐octahedral, octahedral, dealloyed, and nanostructured Pt‐Ni‐Co catalysts was evaluated and compared to that of binary Pt‐based parents . Luo et al and Li et al observed an enhancement of both MA and SA of ternary catalysts than those of parent binary catalysts.…”
Section: Orr On Ternary Pt‐ni‐m Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of nickel and cobalt to alloy with each other and with platinum in various ratios enables their potential use in ternary Pt‐Ni‐Co catalysts . The ORR activity of cubo‐octahedral, octahedral, dealloyed, and nanostructured Pt‐Ni‐Co catalysts was evaluated and compared to that of binary Pt‐based parents . Luo et al and Li et al observed an enhancement of both MA and SA of ternary catalysts than those of parent binary catalysts.…”
Section: Orr On Ternary Pt‐ni‐m Electrocatalystsmentioning
confidence: 99%
“…Octahedral Pt‐Ni‐Co catalysts were synthesized without the use of capping agents or surfactants . In the former case, the resulting shaped ternary catalysts presented higher SA (1.5 times) and MA (1.4 times) than octahedral Pt‐Ni.…”
Section: Orr On Ternary Pt‐ni‐m Electrocatalystsmentioning
confidence: 99%
“…Moreover, from the digital photographs of the activated carbon-supported nanoparticles solution at different reaction temperature, which were shown in Fig. S6 in SI, we found that more Ni could be reduced with increasing the temperature and thus the formation of composition-tunable nanoparticles [23]. In addition to the reaction temperature, the use of benzoic acid was essential to the synthesis of well-defined octahedral PtxNi1−x nanoparticles.…”
Section: Resultsmentioning
confidence: 93%
“…Aran-Ais et al presented a growth study of ternary Pt-Ni-Co nanooctahedra via low temperature, surfactant-free solvothermal synthesis [72]. In a 'one-step' approach, they showed that Ni reduction prevails over Co reduction.…”
Section: Ternary Pt-ni-co Nanoparticlesmentioning
confidence: 99%